2014
DOI: 10.2135/cropsci2013.10.0711
|View full text |Cite
|
Sign up to set email alerts
|

Selenomethionine and Total Methionine Ratio is Conserved in Seed Proteins of Selenium‐Treated and Nontreated Soybean, Flax, and Potato

Abstract: Crop biofortification with Se is widely accepted. However, little is known about the efficiency of selenomethionine (Se‐Met) incorporation into the seed and tuber protein fraction of crops. Here, we report on the efficiency of Se incorporation into the seed and tuber protein fraction of soybean, flax, and potato and the putative identity of some of the proteins that are likely targets for this random pretranslation modification. Soybean, flax, and potato plants received Se using different sodium selenate appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Freshly growing cultures of these two fungal pathogens were removed from storage and maintained on agar medium prior to use. The identity of all pathogens included in this study was confirmed by morphological and molecular methods (Nelson et al 1983;Geiser et al 2004;De Boer et al 2012;Peters et al 2014).…”
Section: Pathogen Strainsmentioning
confidence: 72%
See 4 more Smart Citations
“…Freshly growing cultures of these two fungal pathogens were removed from storage and maintained on agar medium prior to use. The identity of all pathogens included in this study was confirmed by morphological and molecular methods (Nelson et al 1983;Geiser et al 2004;De Boer et al 2012;Peters et al 2014).…”
Section: Pathogen Strainsmentioning
confidence: 72%
“…The use of Se in crop biofortification for enhancing secondary metabolite production and improving Se content in crops for human consumption has been widely reported for several crops (Malagoli et al 2015), including Brassica and Allium species (Terry et al 2000), potato (Turakainen et al 2004a(Turakainen et al , 2004bFofana et al 2014;de Oliveira et al 2019), broccoli (Lyi et al 2005), lettuce (Ramos et al 2010), tomato (Brummell et al 2011), soybean and flax (Fofana et al 2014) and maize (Bocchini et al 2018). This study confirmed the above findings of increased Se uptake and production of health-promoting secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations